Brain and hepatic Hsp70 protein levels in heat-acclimated broiler chickens during heat stress - Guerreiro, EN [UNESP]; Giachetto, PF [UNESP]; Givisiez, PEN [UNESP]; Ferro, JA [UNESP]; Ferro, MIT [UNESP]; Gabriel, Jane Eyre [UNESP]; Furlan, Renato Luis [UNESP]; Macari, Marcos [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2004)
In the present study we have investigated the effects of heat acclimation on brain and hepatic Hsp70 protein levels and body temperature of broiler chickens in response to gradual heat stress. Two groups of broilers were raised up to 47 days of age under distinct temperature conditions: thermoneutral (TN, according to bird age) or hot environmental (HS, 31-33°C). At 46 days of age, the birds reared at high ambient temperature were transferred to thermoneutrality conditions. After 18 h, these birds and the birds reared at thermoneutral temperature were submitted to gradual heat stress in a climatic chamber so that environment temperature was increased from 28 to 40ºC at a rate of 2ºC/h. Colonic temperature was measured using a thermometer sensor probe at each two hours, and hepatic and brain tissues were collected immediately after slaughter in order to assess Hsp70 protein level by Western blotting analysis. The colonic temperatures of birds reared at high temperature increased steeply during the first 2 h of heat stress (1.06ºC/h) and more slowly thereafter (0.59ºC/h). Broilers reared at thermoneutral temperature showed a small increase in the first 4 h of heat stress (0.18ºC/h) and then colonic temperature increased sharply (0.72ºC/h). Nevertheless, both groups presented similar final colonic temperature by the end of the stress period. Hsp70 levels (ng Hsp70 µg total protein-1) did not change in the liver or brain of the birds reared at high temperature. on the other hand, both liver and brain Hsp70 levels increased significantly during heat stress in the animals reared at thermoneutrality, with a higher expression of this peptide in brain tissue.
Keywords: acclimation; Broiler chickens; heat shock protein; Heat stress